Prevalence of phlebitis in adult patients admitted to a university hospital - Angela Elisa Breda Rodrigues de Souza; João Lucas Campos de Oliveira; Denise Costa Dias; Anair Lazzari Nicola (Rev Rene)
Objective: to identify the prevalence of phlebitis, related to demographic and clinical variables, in peripheral intravenous therapy in adult patients admitted to a university hospital in Paraná, PR, Brazil. Method: this is an observational research, cross / prospective with a quantitative approach, carried out in three units of the hospital. Data collection took place from October 2012 to August 2013, using a form to extract demographic and clinical variables from patients suitable to preestablished eligibility requirements. For analysis, we used the calculation of point prevalence. Results: from 221 analyzed by venous access, there were 42 with presence of the clinical criteria definition of phlebitis. It was found a prevalence of phlebitis in men; with evolution degree of 2; venous punctures were located on the back of the hand; 22G caliber/diameter catheters; with residence time of three days. Conclusion: It was concluded that through the prevalence of known phlebitis, nursing actions for the prevention and management of the event can be (re)designed.